Price volatility spillover of Indian onion markets: A comparative study - KANCHAN SINHA; SANJEEV PANWAR; WASI ALAM; K N SINGH; BISHAL GURUNG; RANJIT KUMAR PAUL; ANIRBAN MUKHERJEE (The Indian Journal of Agricultural Sciences, 2023)
To investigate the interdependence between Indian onion markets in terms of price volatility, the present study was conducted in four different vital onion markets in India, viz. Mumbai, Nashik, Delhi and Bengaluru. The long term monthly data, from March, 2003 to September, 2015 was collected from the website of agmarknet.nic.in. We have employed the VEC-MGARCH model to estimate mean and volatility spillover simultaneously among the different markets and also examined the nature of dynamic correlation using the DCC model. The presence of mean and volatility spillover was found between the markets. This type of significant interaction between the volatility of different markets is highly useful for cross market hedging and for sharing of common information by market participants. The empirical results also suggest for a very close observation on different market behavioral pattern since, “news” in one market may impact other market through the number of interdependencies. Key words: Dynamic conditional correlations, Market behavior, Price volatility spillover